Is the Intent of Mergers and Acquisitions Perceptual: Evidence from the Link between CEO Compensation and Decision of Mergers and Acquisitions - Li, Xiaoran (2010)
The increasing frequency and deal size of mergers and acquisitions (M&A) in market contradict the general agreement that a large proportion of M&A fail to benefit shareholders of acquiring firms. The reasons of taking M&A for companies can be complex, but it is possible that people factor risk the success of M&A from the beginning. As CEO compensation considered to be a force for CEOs to make effort to engage their companies to M&A, failure of M&A to some extent depends on perceptual factor.